Optimalisasi Kompetensi Literasi Digital Guru PAI Melalui Program KKG Kota Sabang - Yusniar, Yusniar; Mahmud, Salami; Zulfatmi, Zulfatmi; Aisyah, Aisyah (FITRAH: International Islamic Education Journal, 2024)
This study explores the digital literacy competencies of Islamic Religious Education (IRE) teachers in Sabang City. It also examines the role of Teacher Working Groups (KKG) in enhancing these competencies, as well as the strategies implemented by KKG to support teacher development. A mixed-methods approach was adopted, involving data collection through interviews, observations, questionnaires, and documentation. The findings indicate that the digital literacy competencies of IRE teachers vary, from basic technology usage to the creative and effective integration of technology in teaching. Factors influencing the development of digital literacy competencies include, such as, experience, training, and institutional support. The KKG program significantly contributes by implementing developmental initiatives such as technology-based training, workshops, seminars, and sharing best practices in digital media usage. The strategies applied by KKG include developing curricula for technology-based training, mentoring teachers, and providing continuous monitoring to ensure effective implementation. Furthermore, KKG promotes collaboration among teachers, which enhances the effectiveness of digital learning and mastery of digital media as teaching tools. Abstrak Penelitian ini bertujuan untuk mengeksplorasi kompetensi literasi digital guru Pendidikan Agama Islam (PAI) di Kota Sabang, peran Kelompok Kerja Guru (KKG) dalam meningkatkan kompetensi tersebut, dan strategi yang diterapkan oleh KKG. Penelitian ini menggunakan pendekatan metode campuran, dengan pengupulan data melalui wawancara, observasi, kuesioner, dan dokumentasi. Temuan menunjukkan bahwa kompetensi literasi digital guru PAI bervariasi, mulai dari kemampuan dasar penggunaan teknologi hingga kemampuan mengintegrasikan teknologi dalam pembelajaran secara kreatif dan efektif. Faktor-faktor yang memengaruhi pengembangan kompetensi literasi digital guru PAI meliputi pengalaman, pelatihan, dan dukungan institusi. Program KKG berkontribusi signifikan melalui inisiatif pengembangan, seperti pelatihan berbasis teknologi, lokakarya, seminar, dan berbagi praktik terbaik dalam penggunaan media digital. Strategi yang diterapkan KKG meliputi pengembangan kurikulum pelatihan berbasis teknologi terbaru, pendampingan kepada guru, serta pemantauan berkelanjutan untuk memastikan penerapan yang efektif. Selain itu, KKG mendorong kolaborasi antar guru yang berkontribusi pada peningkatan efektivitas pembelajaran digital dan penguasaan media digital sebagai alat pengajaran.